(untitled) (Perspectivas de las Ciencias Económicas y Jurídicas, 2023)
The main objective of the study was to identify the main factors that influence the retention of IT talent. From this purpose, in the first place, the theoretical framework was reviewed about the current context of the IT industry and the shortage of talent that exists in it, the importance of talent retention and the negative impact of its lack of management. Regarding the methodological approach, to meet the objective, a quantitative study was carried out, through the analysis of data collected through a questionnaire, answered by 420 IT profile professionals. Finally, it was possible to demonstrate and conclude that, in addition to economic incentives, opportunities to develop knowledge, both positive and negative feedback and factors related to sustainability and the work environment are key to retaining this type of profile.